2018
DOI: 10.1155/2018/8369262
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Motor Outcome of the Untrained Hand by Action Observation: Mirror Visual Feedback, Video Therapy, or Both Combined—What Is More Effective?

Abstract: Action observation (AO) allows access to a network that processes visuomotor and sensorimotor inputs and is believed to be involved in observational learning of motor skills. We conducted three consecutive experiments to examine the boosting effect of AO on the motor outcome of the untrained hand by either mirror visual feedback (MVF), video therapy (VT), or a combination of both. In the first experiment, healthy participants trained either with MVF or without mirror feedback while in the second experiment, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 70 publications
(94 reference statements)
1
22
0
Order By: Relevance
“…In a short-term study in which the participants performed 20 blocks of finger sequence abduction tasks for 15 s, MTr achieved greater functional improvement in the inactive limb compared with active vision pattern 21. In three long-term studies in which participants performed comprehensive hand performance tests for 20 or 10 min daily for 4 days, there were significant improvements in motor performance in the untrained hand with MTr compared with active vision 23–25…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In a short-term study in which the participants performed 20 blocks of finger sequence abduction tasks for 15 s, MTr achieved greater functional improvement in the inactive limb compared with active vision pattern 21. In three long-term studies in which participants performed comprehensive hand performance tests for 20 or 10 min daily for 4 days, there were significant improvements in motor performance in the untrained hand with MTr compared with active vision 23–25…”
Section: Resultsmentioning
confidence: 98%
“…Thus, 14 randomised controlled trials were included in the final analysis (figure 1). Nine studies were conducted in Germany18–26 (including one in collaboration with China) 19. Two studies were conducted in Australia,27 28 and the other three studies were performed in Japan,29 the Netherlands30 and the USA 31.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MT is a visual feedback training procedure in which an individual rehearses a limb movement by reflected movements of the nonparetic side in a mirror as if it were the affected side. In healthy subjects, mirror visual feedback can increase actionrelated motor competence in an untrained hand (Bähr et al 2018). In stroke patients, randomized prospective trials of MT have shown that although some recovery occurred with sham treatments, MT led to significantly greater recovery of upper extremity function (Gurbuz et al 2016;Lim et al 2016).…”
Section: Introductionmentioning
confidence: 99%